A building operational carbon emissions database of 362 Chinese cities: Construction process and spatiotemporal characteristic analysis - Qi Wang; Xinyu Jia; Yang Zhao; Hao Zhou; Xinghui Zhang; Borong Lin; Cong Zhang (Developments in the Built Environment)
The existing calculation methods of city building carbon emissions based on energy audits, city statistics and energy balance sheets have problems such as time-consuming and labour-intensive, missing data and large errors, resulting in the lack of a complete and accurate database of city building carbon emissions in China. To address this, the calculation method based on city statistical data (CSD-M) and the calculation method based on provincial energy balance sheets (PEB-M) were used to calculate the carbon emissions from city buildings. The PEB-M was corrected using CSD-M results, reducing the error to 12.8%. Based on CSD-M and modified PEB-M, a database of building carbon emissions in 362 Chinese cities was developed. Finally, the spatio-temporal characteristics of city building carbon emissions in China were analysed, and the current situation of carbon emissions in different cities was compared. This study provides a basis for future carbon reduction policies tailored to city characteristics.